2010
DOI: 10.1213/ane.0b013e3181c84e33
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perfusion Pressure on Gastric Tissue Blood Flow in an Experimental Gastric Tube Model

Abstract: Blood flow in the upper part of the gastric tube is decreased compared with more proximal sites. Gastric tissue blood flow does not increase with increased perfusion pressure. Therefore, it is not recommended to increase MAP to supranormal levels to increase anastomotic tissue blood flow and reduce postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…122 Using vasopressors to increase the mean arterial blood pressure to greater than 70 mm Hg has not been shown to have a beneficial effect on the microcirculation. 120 However, the meta-analysis that was incorporated into the recent OPTIMISE trial, which compared the use of cardiac output-guided hemodynamic therapy using fluids and dopexamine with usual care, found a reduction in complication rates. 103 The findings of a metaregression analysis also suggest that dopexamine infusion at low dose, providing mild inotropic and vasodilatory effects, is associated with improved outcomes following major surgery.…”
Section: Cardiovascular Issuesmentioning
confidence: 99%
“…122 Using vasopressors to increase the mean arterial blood pressure to greater than 70 mm Hg has not been shown to have a beneficial effect on the microcirculation. 120 However, the meta-analysis that was incorporated into the recent OPTIMISE trial, which compared the use of cardiac output-guided hemodynamic therapy using fluids and dopexamine with usual care, found a reduction in complication rates. 103 The findings of a metaregression analysis also suggest that dopexamine infusion at low dose, providing mild inotropic and vasodilatory effects, is associated with improved outcomes following major surgery.…”
Section: Cardiovascular Issuesmentioning
confidence: 99%
“…Optimally, local perfusion pressure and flow would be monitored during the operation and during the first postoperative days. However, until now this has only been done in experimental settings (53)(54)(55)(56)(57)(58).…”
Section: Haemodynamics Vs Integrity Of the Anastomosismentioning
confidence: 99%
“…Some experimental perfusion or microcirculation monitor techniques have been described in oesophagus surgery (53)(54)(55)(56)(57)(58)(59) (52,56,57). However, large prospective clinical studies are needed to show the usefulness of these techniques in influencing outcome.…”
Section: Monitoring Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…86 However, several recent animal studies have suggested that treatment of intraoperative hypotension with norepinephrine does not cause any reduction in gut blood flow. 87,88 An ideal fluid regimen for major surgeries, including oesophageal surgery, is individualised and optimises cardiac output and oxygen delivery, while avoiding excessive fluid administration. There is some evidence that fluid therapies which are designed to achieve individualised and specific flow-related haemodynamic end-points, such as stroke volume, cardiac output or measures of fluid responsiveness, such as stroke volume variation (collectively referred to as goal-directed fluid therapy), may provide a superior alternative to fixed regimens or those based on static measures of cardiac filling.…”
Section: Fluids Inflammation and The Glycocalyxmentioning
confidence: 99%